Excellence in Scholarship
XX, 282 p.
Keywords: Teachers empower both the next generation of learners and educators. Communities value the intricate roles and responsibilities of teachers: many of whom who go beyond the tangibles to cater to the learning needs of their students. The multidimensional and multifaceted relationship between teacher-education providers and teachers is a complex one. At one end of the spectrum sits the scholarship of teaching while at the enacted zone sits standards-based praxis. Teacher education and scholarship of teaching provides the avenue to demonstrate this interaction of knowledge, pedagogy, research and broadly, scholarship. Unfortunately, there is no strong consensus about the value of pedagogical preparation for teachers. This monograph highlights the broad focus on how education draws its knowledge base from various disciplines; advancing that education itself can become a plethora for shared discourse and reflection. The chapters provide fresh demonstrated understanding into practice-enabled research directions and emphasise the position of research-based praxis in both schools and in institutions entrusted with teacher education. Importantly, the monograph demonstrates the two-way communication between the community and teacher educators about knowledge, experiences, values and diversity and to add value with the sole aim to enhance learning. It highlights education is a collective endeavour in that education and teacher education are subsets of the community, and deliberations in communities add important synergy to education’s evolution and revolution. Thus, the process of inquiry is fundamental in education, and implies transcending traditional discipline-bound knowledge and processes. This monograph provides the challenge to educators that no single or specific discipline directs educational development and enrichment, nor does the latter exclude any.